Pengaruh Iklim Organisasi Terhadap Produktivitas Kerja Pegawai Pada Dinas Komunikasi Dan Informatika Kabupaten Bima - Ansyar Ansyar; Firmansyah Kusumayadi (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research aims to determine the influence of Organizational Climate on the Work Productivity of Bima Regency Communication and Information Service Employees. This research is of associative type. The population used was all service employees as many as 61 respondents using purposive sampling techniques to obtain a sample of 40 respondents. The research instrument used is a Likert scale questionnaire with data analysis techniques, validity test, reliability test, simple regression analysis, simple correlation analysis, determination test and T test. The results of this research conclude that there is a significant influence between organizational climate on employee work productivity in Bima Regency Communication and Information Service with a calculated t value of 15.791 which is greater than the t table of 2.026. The determination test shows that employee work productivity is influenced by organizational climate by 86.8%, while the remaining 13.2% is influenced by other factors or variables not included in this research.